2016
DOI: 10.1093/protein/gzw027
|View full text |Cite
|
Sign up to set email alerts
|

Steric interactions determine side-chain conformations in protein cores

Abstract: We investigate the role of steric interactions in defining side-chain conformations in protein cores. Previously, we explored the strengths and limitations of hard-sphere dipeptide models in defining sterically allowed side-chain conformations and recapitulating key features of the side-chain dihedral angle distributions observed in high-resolution protein structures. Here, we show that modeling residues in the context of a particular protein environment, with both intra- and inter-residue steric interactions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…In prior work, we demonstrated that one can repack the side‐chains of residues in protein cores using only hard‐sphere repulsive interactions in the context of a calibrated atomistic model . In this study, we investigate whether the same approach can predict the conformations of amino acid side‐chains at protein‐protein interfaces and in transmembrane proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior work, we demonstrated that one can repack the side‐chains of residues in protein cores using only hard‐sphere repulsive interactions in the context of a calibrated atomistic model . In this study, we investigate whether the same approach can predict the conformations of amino acid side‐chains at protein‐protein interfaces and in transmembrane proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that steric interactions between the side‐chain of a residue and the rest of the protein are necessary to accurately predict the side‐chain dihedral angles of amino acid residues . However, to obtain a lower bound on the prediction accuracy of the hard‐sphere model, we also predicted the side‐chain conformations for each amino acid without the rest of the protein, that is, each residue modeled as a dipeptide mimetic (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations